Færð: App for Road Conditions - Dovydas Stankevicius 1994-; Gunnhildur Finnsdóttir 1977-; Telma Guðbjörg Eyþórsdóttir 1992- (2016)
Færð is a mobile app where travelers on Icelandic roads can access information on road conditions and other useful data regarding their trip. It consists of two main components, a mobile client with a simple user interface and a back-end where data is collected, merged and parsed. It is designed with both Icelandic locals and an ever increasing number of foreign visitors in mind. Færð was created by three students at Reykjavík University with support from The Icelandic Road and Coastal Administration (Vegagerðin).